The speculum of Archbishop Thomas Secker - Secker, Thomas, 1693-1768 (Church of England Record Society (Series), 1995)
The Speculum compiled by Archbishop Thomas Secker (1758-68) is a major source for our understanding of the position of the Church of England in the mid-eighteenth century. A parish by parish digest of the returns submitted to the archbishop between 1758 and 1761, in the main for the diocese of Canterbury but including several others. It contains very full information on such matters as the size and social structure of the parishes; the names and qualifications of the clergy; their wealth; and their relations with Roman Catholics and protestant dissenters. Part of the significance of the Speculum is its witness of the pastoral pressure applied by Secker, allowing the historian to assess how far an energetic archbishop was able to improve the standards of pastoral provision in the parishes under his care. This edition has attempted to preserve the spelling and capitalisation of the original, and editorial notes give biographical information on the large number of persons mentioned in the text, as well as identifying other textual allusions. JEREMY GREGORY is Lecturer in History at the University of Northumbria.